The role of learner creativity in L2 semantic fluency. An exploratory study. (December 2021) - Fernández-Fontecha, Almudena
Abstract: Research about individual learner variables in L2 learning has not yet addressed in depth creativity as potentially relevant in the field. This study seeks to examine whether creativity is related to the L2 lexical production of a group of 35 12th grade Spanish EFL (English as a Foreign Language) learners. Four EFL semantic fluency tasks are used to obtain the vocabulary activated in the learner's mental lexicon as a response to four semantic categories: beach, box, countryside and fun . Creativity is measured via the PIC-J Test (Artola et al., 2008), based on Torrance (1990) and Guilford (1967), and validated for the assessment of this construct in Spanish secondary education students. While the findings reveal a significant positive relationship between all measures of creativity and EFL semantic fluency in the four categories, EFL proficiency level and semantic fluency only correlate in some categories. The most creative learners retrieved a wider variety of words and produced more uncommon responses, a result which is consistent with recent neural and cognitive research on creativity. These findings are suggestive of the need for considering creativity and its various dimensions in L2 teaching. Highlights: Creativity and related measures might be having some effect on EFL semantic fluency regardless of proficiency. Creativity is related to the production of a wider variety of words in L2. Creativity is related to the production of more uncommon responses in L2. EFL proficiency level and EFL semantic fluency only correlate in some cases. Findings suggestive of the need of considering creativity in L2 teaching.